Effect of a dairy diet on nasopharyngeal mucus secretion. (4th September 2018) - Frosh, Adam; Cruz, Carina; Wellsted, David; Stephens, Joanna
Abstract : Objectives/Hypothesis: To examine the effects of dairy versus nondairy diets on self‐reported levels of nasopharyngeal mucus secretion. Study Design: Prospective, randomized, double‐blinded controlled study. Methods: Twenty‐six men and 82 consecutive women over the age of 15 years attending the otolaryngology department at East and North Hertfordshire NHS Trust who reported experiencing increased levels of nasopharyngeal mucus secretions were selected for a double‐blinded trial of dairy versus dairy‐free dietary supplementation for the last 4 days of a 6‐day dairy‐free diet. Main outcome measures were comparisons of mean daily reporting of subjective levels of nasopharyngeal secretions by linear scoring (1–100) and by an ordinal scale of 1 to 4. On each day, t tests were used to compare differences. Results: There was a significant reduction in the reported linear secretion score seen from day 1 to 4 in nondairy ( t [53] = 4.39, P < .01) and in dairy ( t [53] = 3.94, P < .01) arms. There was a significant increase in secretion score days 4 to 7 in the dairy arm ( t [53] = −2.56, P = .01), and a continued but nonsignificant reduction in the nondiary arm ( t [53] = 1.54, P = .13, with an overall significant reduction between day 1 and 7 in the nondairy arm ( t [53] = 4.79, P < .00). In the ordinal secretion scale, both dairy arm ( t [53] = 2.754, P < .01) and nondiary arm ( t [53] = 5.52, P < .01) scores decreased significantly from days 1 to 4. There was a significant decrease in scores from days 1 to 7 in the nondairy group ( t [53] = 5.12, P < .01). Conclusions: In this blinded trial, a dairy‐free diet was associated with a significant reduction in self‐reported levels of nasopharyngeal secretions in adults who previously complained of persistent nasopharyngeal mucus hypersecretion. Level of Evidence: 1b Laryngoscope, 129:13–17, 2019